Hyperpolarized Krypton 83Kr as a novel contrast agent for pulmonary magnetic resonance imaging (MRI) - Alrumyan, Saleh Abdulkareem A. (2019)
This PhD thesis is devoted to the problem of visualization of respiratory organs by magnetic resonance imaging and is aimed at developing a method of magnetic hyperpolarization of noble gases and developing a method for visualizing lungs using inert noble gases. According to the World Health Organization, respiratory diseases are considered to be the most common (Organization et al., 2011).